Mutual Cooperation Culture of Pakpak Ethnic Communities North Sumatera: As Far As The Student Understands It? - Hodriani; Julia Ivanna; Surya Dharma (Polit Journal Scientific Journal of Politics, 2021)
The biggest challenge of the Indonesian people today is the weakening of national identity, which is marked by the fading sense of social solidarity. Egocentrism behavior is often seen and become something that is common in today's patterns of social relations. The culture of gotong royong is no longer used as a community tradition that is the wealth of the archipelago. This challenge is increasingly apparent because most of the younger generation seems to lack the awareness to preserve various traditions of the Indonesian community's gotong royong. Though gotong royong is a character as well as the national identity of the Indonesian nation that distinguishes it from other nations. Starting from this background, this study aims to find out how students' understanding of the mutual cooperation culture in the Pakpak ethnic community of North Sumatra. This research uses descriptive analytical method. The research subjects were Civic Education and Pancasila Department, University of Medan State. The results showed that the low understanding of students towards various cultures of gotong royong carried out by the Pakpak ethnic community in North Sumatra. This affects the mindset and actions of students to understand and preserve various cultures of gotong royong. From the results of this study it is necessary to develop a learning model that is able to build student awareness of gotong royong culture. The results showed that the low understanding of students towards various cultures of gotong royong carried out by the Pakpak ethnic community in North Sumatra. This affects the mindset and actions of students to understand and preserve various cultures of gotong royong. From the results of this study it is necessary to develop a learning model that is able to build student awareness of gotong royong culture. The results showed that the low understanding of students towards various cultures of gotong royong carried out by the Pakpak ethnic community in North Sumatra. This affects the mindset and actions of students to understand and preserve various cultures of gotong royong. From the results of this study it is necessary to develop a learning model that is able to build student awareness of gotong royong culture.